Analisis Kesalahan Siswa dalam Menyelesaikan Soal Matematika Materi Perkalian Menggunakan Metode Lattice - Elsa Wulandari (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze students’ errors in solving multiplication problems using the lattice method within a junior high school context. Employing a descriptive qualitative approach, the research involved 40 seventh-grade students selected through purposive sampling. Data were collected through essay-based online tests designed to capture conceptual, procedural, and operational dimensions of student performance. The findings reveal that students’ errors are predominantly rooted in conceptual misunderstandings rather than procedural inaccuracies, indicating a critical gap between algorithmic execution and conceptual comprehension. Furthermore, students demonstrate inconsistent mathematical representations, suggesting limitations in integrating visual structures with numerical reasoning during problem-solving processes. While the lattice method provides structural support for procedural organization, it does not inherently ensure conceptual clarity or representational accuracy. These results highlight the necessity of instructional strategies that emphasize diagnostic assessment, conceptual reinforcement, and the development of mathematical literacy. The study contributes to the theoretical understanding of error patterns in mathematics learning and offers methodological insights for designing adaptive and cognitively responsive teaching interventions.